PENGARUH KOMPENSASI, STANDAR KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Faiz Sultan Albab; Saryadi Saryadi; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2014)
The Compensation, standard of work and working environment is a supporting factor for achieve the high performance of employees in order to get optimal business profits. If the company has a good compensation, standard of work  and working environment, then the high employee performance can be achieved. The problems of this research are still there employees who violate standard of work, there are employees who have bad habits in work, and employee performance which shows the numbers fluctuate and tend to decline. Technique of collecting data using questionnaires distributed to 50 employees as the population in this study using census method sales of PT. Nasmoco Kaligawe Semarang. The Data were analyzed with quantitative analysis using validity, reliability test, the coefficient of determination, simple linear regression, multiple linear regression, T test and F test with SPSS. The conclusion of this analysis study is the 48 % of respondents said the compensation is fair, 48 % of respondents said the standard of work is quite good, 46 % of respondents said the working environment in both categories and 28 % of the respondents have a high employee performance. Variable compensation, standards of work, and the work environment has an influence on employee performance variables partially or simultaneously.